Western Interest dalam Proses Perkembangan Negara Israel (1917-1948) Sebagai Akar Utama Konflik Israel-Palestina - Tika Tazkya Nurdyawati (Ampera: A Research Journal on Politics and Islamic Civilization, 2020)
The Israeli-Palestinian conflict which is often found to continue for more than 7 decades is inseparable from the root of the problem itself, namely; designation of the Palestinian territories as a national home for the Jews which would later lead to Israeli independence in 1948. Referring to the Balfour Declaration 1917 under the British decision, the massive migration of Jews from Europe to Palestine was inseparable from the benefits that were gained by Western hegemonies in the West. the winner of the war at the time. This can be studied using a realism perspective which views the state as a rational actor with all its decisions under the national interest. Using the literature review method, this article tries to answer whether the tension that occurs in the Israeli-Palestinian conflict is based solely on differences in religious identity between the two? Or are there interests of several parties that do not appear on the surface? Why can the annexation case in the formation of an Israeli state that violates international law continue without strict sanctions? The economic and political motivated interests of the West and the connection of Zionism in the founding of the state of Israel will be examined as concrete evidence. This article is expected to be useful as a reference for later literature for similar research.